Assessment of Technetium-99m Labeled Macroaggregated Albumin Rhinoscintigraphy for the Measurement of Nasal Mucociliary Transport Rate: Intratest, Interobserver, and Intraobserver Reproducibility. (5th March 2014) - Dostbil, Zeki; Dag, Yusuf; Cetinkaya, Ozlem; Akdag, Mehmet; Tasdemir, Bekir
Abstract : Objectives. The measurement of mucociliary transport velocity by rhinoscintigraphy with Tc-99m-macroaggregated albumin ( 99m Tc-MAA) is reliable measure of mucociliary clearance. The aim of this study is to assess the intratest, interobserver, and intraobserver reproducibility of nasal mucociliary transport rate (NMTR) measurement. Materials and Methods. Twenty-two subjects were evaluated to determine intratest reproducibility and a group of 35 subjects was examined to determine inter- and intraobserver reproducibility. Rhinoscintigraphy with 99m Tc-MAA was used to measure NMTR in all study subjects. Paired NMTR measurements were compared using a range of statistical methodologies. Intraclass correlation coefficients (ICC) and repeatability coefficients and Bland-Altman plots were applied to assess the degree of intratest, interobserver, and intraobserver variation. Results. Statistical analysis of test and retest experiments demonstrated the statistical equivalence of intratest NMTR measurements, interobserver NMTR measurements, and intraobserver NMTR measurements. The intratest ICC, interobserver ICC, and intraobserver ICC were 0.96, 0.83, and 0.91, respectively, indicating that intratest and intraobserver reproducibility are excellent and interobserver reproducibility is good. Conclusions. Rhinoscintigraphy using 99m Tc-MAA results in highly reproducible measurement of NMTR. The use of radionuclide imaging in measuring NMTR results in excellent intratest and intraobserver reproducibility and good interobserver reliability.